The Influence Of Emotional Intelligence And Self Efficasy On Employee Performance At The Regional Secretariat Of Kaur Regency - Nugraha, Refky Sapta; Hanilah, Siti; Ferina, Zahrah Indah (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Lack of emotional intelligence and self efficacy will make performance not good, which is indicated by the indiscipline of employees at work. Therefore, this study aims to determine the effect of emotional intelligence and self efficacy on employee performance at the Regional Secretariat of Kaur Regency. The sample in this study was 63 people consisting of civil servants and honorary employees who worked in the Regional Secretariat of Kaur Regency. Data were collected using a Likert scale questionnaire. The data obtained were analyzed using multiple linear regression analysis, which was tested at a 95 percent confidence level. The results showed that the regression equation of the results of this study was Y = 17.075 + 0.399 X1 + 0.545 X2. This means that the level of emotional intelligence and self efficacy has a positive effect on employee performance at the Regional Secretariat of Kaur Regency. This can illustrate that if the variable level of emotional intelligence and the self efficacy variable increases, the performance of employees at the Regional Secretariat of Kaur Regency will also increase. The coefficient of determination (R2) of the research results is 54.4 percent. Thus it can be concluded that the level of emotional intelligence and self efficacy affects employee performance at the Regional Secretariat of Kaur Regency by 54.4 percent while the remaining 45.6 percent (100 - 54.4 = 45.6) is explained (influenced) by other variables outside the model research. The level of emotional intelligence and self efficacy together affects employee performance at the Regional Secretariat of Kaur Regency with a significance of 0.000 less than 0.05. This shows that an increase in emotional intelligence and self efficacy results in an increase in employee performance at the Regional Secretariat of Kaur Regency.